Cardiac involvement in adult and juvenile idiopathic inflammatory myopathies. Issue 2 (27th September 2016) - Schwartz, Thomas; Diederichsen, Louise Pyndt; Lundberg, Ingrid E; Sjaastad, Ivar; Sanner, Helga
Abstract : Idiopathic inflammatory myopathies (IIM) include the main subgroups polymyositis (PM), dermatomyositis (DM), inclusion body myositis (IBM) and juvenile DM (JDM). The mentioned subgroups are characterised by inflammation of skeletal muscles leading to muscle weakness and other organs can also be affected as well. Even though clinically significant heart involvement is uncommon, heart disease is one of the major causes of death in IIM. Recent studies show an increased prevalence of traditional cardiovascular risk factors in JDM and DM/PM, which need attention. The risk of developing atherosclerotic coronary artery disease is increased twofold to fourfold in DM/PM. New and improved diagnostic methods have in recent studies in PM/DM and JDM demonstrated a high prevalence of subclinical cardiac involvement, especially diastolic dysfunction. Interactions between proinflammatory cytokines and traditional risk factors might contribute to the pathogenesis of cardiac dysfunction. Heart involvement could also be related to myocarditis and/or myocardial fibrosis, leading to arrhythmias and congestive heart failure, demonstrated both in adult and juvenile IIM. Also, reduced heart rate variability (a known risk factor for cardiac morbidity and mortality) has been shown in long-standing JDM. Until more information is available, patients with IIM should follow the same recommendations for cardiovascular risk stratification and prevention as for the corresponding general population, but be aware that statins might worsen muscle symptoms mimicking myositis relapse. On the basis of recent studies, we recommend a low threshold for cardiac workup and follow-up in patients with IIM.